The Prebiotic Effects of Oats on Blood Lipids, Gut Microbiota, and Short-Chain Fatty Acids in Mildly Hypercholesterolemic Subjects Compared With Rice: A Randomized, Controlled Trial - Xu, Dengfeng; Feng, Meiyuan; Chu, YiFang; Wang, Shaokang; Shete, Varsha; Tuohy, Kieran M.; Liu, Feng; Zhou, Xirui; Kamil, Alison; Pan, Da; Liu, Hechun; Yang, Xian; et al. (Frontiers in Immunology, 2021)
Phytochemicals derived from oats are reported to possess a beneficial effect in dyslipidemia, specifically by loweing total and LDL-cholesterol. However, deeper insights into its mechanism remain unclear. In this randomized controlled study, we assigned 210 mildly hypercholesterolemic subjects from three study centers across China (Beijing, Nanjing and Shanghai) to consume 80 g oats or rice daily for 45 days. Serum lipid profiles, short chain fatty acids (SCFA), and fecal microbiota were measured. The results showed that total cholesterol (TC), and non-high-density lipoprotein cholesterol (non-HDL-C) decreased significantly with both oats and rice intake after 30 and 45 days. The reduction in TC and non-HDL-C was greater in the partcipants consuming oats compared to rice at day 45 (P=0.011 and 0.049 respectively). Oat consumption significantly increased the abundance of Akkermansia muciniphila and Roseburia, and the relative abundance of Dialister, Butyrivibrio, Paraprevotella and decreased unclassified f-Sutterellaceae. In the oat group, Bifidobacterium abundance was negatively correlated with LDL-C (P=0.01, r= -0.31) and, TC and LDL-C were negatively correlated to Faecalibacterium prausnitzii (P=0.02, r= -0.29; P=0.03, r= -0.27, respectively). Enterobacteriaceae, Roseburia and Faecalibacterium prausnitzii were positively correlated with serum butyric acid and valeric acid concentrations, and negatively correlated to isobutyric acid. HDL-C was negatively correlated with valeric acid (P=0.02, r= -0.25) and total triglyceride (TG) was positively correlated to isovaleric acid (P=0.03, r=0.23). Taken together, oats conusmption significantly reduced TC and LDL-C, and also mediated a prebiotic effect on gut microbiome. Akkermansia muciniphila, Roseburia, Bifidobacterium and Faecalibacterium prausnitzii, and serum SCFA correlated with oat induced changes in serum lipids, suggesting prebiotic activity of oats to modulate gut microbiome could contribute towards its cholesterol-lowering effect.